Cosmeceuticals: A Newly Expanding Industry in South Africa - Fikisiwe C. Gebashe; Devashan Naidoo; Stephen O. Amoo; Nqobile A. Masondo (Cosmetics, 2022)
Africa is counted amongst the cosmetic market contributors; however, South Africa’s remarkable plant diversity is still largely untapped in terms of its potential for medicinal and cosmetic purposes. Thus, we aim to provide a critical assessment of the advancements made in South African cosmeceuticals with emphasis towards online local companies/brands that are manufactured by small, medium and micro enterprises (SMMEs). For the current study, we limited our search of herbal cosmeceutical products to SMMEs with online websites, or products traded in other online cosmetic directories such as ‘Faithful to Nature’ and ‘African Botanicals’ using a simple Google search. We recorded more than 50 South African SMME companies/brands involved in the trade of cosmeceuticals. Skin and hair care were the major product categories widely traded in these online platforms. Furthermore, few patents were recorded from South African researchers and institutions thereof, which is quite alarming considering the extensive research that has been undertaken to study these commercially valuable plants. Based on the increasing number of new products and the wide pool of economically important plants coupled to their associated rich indigenous knowledge systems, the cosmeceutical sector can contribute to the economy, job creation, entrepreneurship skills, socio-economic development and intellectual property generation.